Klinična presoja kakovosti mamogramov - Rener, Miljeva (Radiology and oncology (Ljubljana), 1999)
Good quality mammogram is characterised by the following features: proper positioning, correct exposition, correct contrast, sharpness, low noise, artefact free execution at acceptable dose. The final product depends on a number of dynamic factors. The most important of them is state-of the art mammographic equipment by optimal calibrated AEC; special attention should be paid to the processing. Highly skilled personel, trained specifically for thiskind of work should continually maintain constant attention to quality control in order to avoid missed and delayed diagnosing.
Keywords: diagnostika; dojke; Mammography; mamografija; Quality control; Technology, radiologic